The multifaceted biomimetic titanium implant promotes bone integration with sequential antibacterial and immune modulation properties - Long Chen; Zili Guo; Guowen Duan; Guodong Zhao; Xinyao Liu; Zian Wang; Yuan Liu; Lingling Bai; Hong Xu; Yan Peng; Lei Qiang; Dongbiao Chang; et al. (Bioactive Materials, 2025)
Titanium (Ti) and its alloy implants often face issues such as insufficient tissue adhesion and vulnerability of the bio inert surface. Given that the long-term stability of implants depends on their perfect integration with the surrounding tissues to withstand various environmental stresses, current research mainly focuses on mimicking the structure of the extracellular matrix. The aim is to promote bone tissue formation through regulation of the immune response by metal ions, thereby enhancing the effectiveness of tissue integration. The self-assembled zinc (Zn)-doped hydroxyapatite nanoparticles (nHA) with polydopamine (PDA) and copper ions (Cu2+) was deposited onto the alkali treated Ti surface to fabricate the P-Zn-Cu/Ti coating. The so-constructed multifunctional coating with bionic micro/nano-structures on the Ti surface can achieve the sequential release of Cu2+ and zinc ions (Zn2+) through the rapid release of Cu2+ in the early stage and the slow release of Zn2+, and followed the functional characteristics of sequentially regulating antibacterial, immune, and osteogenic responses. This study presents a promising strategy to address the challenges associated with the failure of Ti implants, thus promoting the development of implant technology and improving clinical efficacy.